ID: 60: ZINC DEFICIENCY PRIMES THE LUNG FOR VENTILATOR INDUCED LUNG INJURY. Issue 4 (22nd March 2016) - Englert, J; Boudreault, F; Pinilla-Vera, M; Isabelle, C; Arciniegas, A; Quintana, C; Amador, D; Baron, RM; Kho, A; Tschumperlin, DJ
Abstract : Mechanical ventilation is a necessary intervention to support patients with lung injury and the acute respiratory distress syndrome (ARDS), but can also exacerbate injury through mechanical stress-activated signaling pathways. We show that stretch applied to cultured human lung cells, and to mouse lungs in vivo, induces robust expression of metallothionein, a potent anti-oxidant and cyto-protective molecule critical for cellular zinc homeostasis. Furthermore, genetic deficiency of murine metallothionein genes exacerbated lung injury caused by injurious mechanical ventilation, identifying an adaptive role for these genes in limiting lung injury. Stretch induction of metallothionein required zinc and the zinc binding transcription factor MTF-1. We further show that dietary zinc-deficiency in mice potentiates ventilator-induced lung injury, and that plasma zinc levels are significantly reduced in human patients with ARDS compared to healthy and non-ARDS ICU controls, as well as to other critically ill patients without ARDS. Taken together, our findings identify a novel adaptive response of the lung to stretch mediated by metallothionein and zinc. These results demonstrate that failure of stretch-adaptive responses play an important role in exacerbating ventilator-induced lung injury, and identify zinc and metallothionein as targets for developing lung-protective interventions in patients requiring mechanical ventilation.